Gender disparities in K-12 computer science education: Status, contributing factors, and instructional approaches - Kyungbin Kwon; Sang Joon Lee; Keunjae Kim (Computers and Education Open)
This study conducts a systematic review of the literature to investigate gender disparities in K-12 computer science (CS) education. We selected articles published in peer-reviewed journals that focused on both cognitive and affective aspects of computational thinking and CS education at the primary and secondary levels. A total of 29 studies were reviewed, and their findings were synthesized to assess the status of gender disparities, contributing factors, and instructional approaches. The results indicated that gender differences in cognitive and affective dimensions of CS education become more evident as students advance through school, with a greater negative impact on girls. The review identified three interconnected factors contributing to these disparities: socio-cultural influences, educational environments, and individual psychological factors. Additionally, the study proposed instructional approaches to address these issues and recommended future research to fill the current gaps in CS education research.